FACTORS AFFECTING PURCHASING DECISION OF PROPERTY IN BATAM CITY - Candy, Candy; Renato, Rio (LPPM STIE Muhammadiah Bandung, 2021)
Property investment is a stable long-term investment, low risk, and it has protection against inflation. Property investment included housing, shop houses, and apartments. The purpose of this study is to examine the influence of location, neighborhood, structural, financial, and attitude on purchase decision of property in Batam City. This study distributes questionnaires to 250 respondents by using a convenience sampling method. The data analysis uses Partial Least Square-Structural Equation Modeling (PLS-SEM) by examining the outer and inner models. The research results showed that the location, structural, and attitude variables significantly affect purchase decision. Meanwhile, the variable of the neighborhood and financial do not have a significant effect on purchase decision. The R-Square shows that 35.44% of the regression model is explained by the variables in this research, while 64.56% explained by other variables affecting purchase decision.